Selected Topics in Nonlinear Dynamics and Theoretical Electrical Engineering - Kyamakya, Kyandoghere; Halang, Wolfgang A.; Mathis, Wolfgang; Chedjou, Jean Chamberlain; Li, Zhong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book contains a collection of recent advanced contributions in the field of nonlinear dynamics and synchronization, including selected applications in the area of theoretical electrical engineering. The present book is divided into twenty-one chapters grouped in five parts. The first part focuses on theoretical issues related to chaos and synchronization and their potential applications in mechanics, transportation, communication and security. The second part handles dynamic systems modelling and simulation with special applications to real physical systems and phenomena. The third part discusses some fundamentals of electromagnetics (EM) and addresses the modelling and simulation in some real physical electromagnetic scenarios. The fourth part mainly addresses stability concerns. Finally, the last part assembles some sample applications in the area of optimization, data mining, pattern recognition and image processing.
Part I Theory of Chaos and Synchronization and Applications in mechanics, transportation, Communication and Security Related System Concepts -- Part II Systems$1 (BDynamics Modeling and Simulation with applications to real physical systems and phenomena -- Part III Electromagnetics Theory, Modeling and Simulation of Real Physical Electromagnetic Prototypes -- Part IV Theory of Stability and Recent Trends -- Part V Further Application Area- Optimization, Data Mining, Pattern Recognition and Image processing.s
Keywords: Engineering; Computer engineering; Engineering; Electrical Engineering; Nonlinear Dynamics